Gold nanoparticles with high densities of small protuberances on nanocluster cores with strong NIR extinction. Issue 127 (11th December 2015) - Borwankar, Ameya U.; Willsey, Brian W.; Twu, April; Hung, Jessica J.; Stover, Robert J.; Wang, Tianyi W.; Feldman, Marc D.; Milner, Thomas E.; Truskett, Thomas M.; Johnston, Keith P.
Abstract : Plasmonic nanoparticles with sizes well below 100 nm and high near infrared (NIR) extinction are of great interest in biomedical imaging. Abstract : Plasmonic nanoparticles with sizes well below 100 nm and high near infrared (NIR) extinction are of great interest in biomedical imaging. Herein we present ∼60 nm Au nanoparticles with high NIR absorbance at wavelengths ranging from 700 nm to 1100 nm, which were synthesized under kinetic control. A high surface density of protuberances is grown on ∼30 nm nanocluster cores, which are composed of ∼10 nm primary particles. The high NIR extinction is produced by a combination of the close proximity of the primary particles in the cores, the high surface density of protuberances, and the high aspect ratio of the length of the protuberances to the diameter of the primary particles. When the Au precursor was reduced more slowly at a higher pH of 9.3, the growth was thermodynamically controlled and the nanocluster cores relaxed to spheres. This concept of self-assembly during reaction to change the morphology of nanoclusters and decorated nanoclusters, may be expected to be applicable to a wide variety of systems by balancing kinetic and thermodynamic control, along with the colloidal interactions.